Building Resilient Energy Systems - United Nations Economic Commission for Europe (United Nations, 2023)
The ECE Region is at a crossroads and the time is NOW for Member States to put in place policies to drive action that will build a resilient energy system that acknowledges the need for affordable access to energy for quality of life and economic growth, minimizes the environmental impact of the system to create sustainability and meet carbon emission goals, while securing the supply necessary to support society’s needs. The Expert Groups under the UNECE’s Committee for Sustainable Energy (CSE) have collaborated to produce a technical roadmap to balance competing priorities in recognition of today’s very real climate, security, and affordability challenges. It respects Member States’ rights to make decisions that meet their own priorities and as such does not prescribe the specific path forward but lays out the technical considerations that are in critical need of balance at this point in time.